Leveraging Development Communication for Stakeholder Engagement in Arjowinangun's Batik Tourism and Creative Economy Growth - Achmad, Zainal Abidin; Arviani, Heidy; Alamiyah, Syifa Syarifah; Suksmawati, Herlina; Febrianita, Roziana (The Journal of Society and Media, 2025)
This study explores the role of development communication in fostering stakeholder engagement in Arjowinangun Village’s batik tourism initiatives..Researchers aim to position the village as a central hub for batik tulis and establish Woro Srikandi as a leading brand in Pacitan Regency. Using a qualitative, phenomenological approach within development communication, the team gathered data through participant observation, FGDs, and analysis of key documents, including 2023 village data and the RPJMDes (2019-2023). Twelve key informants contributed insights, including village officials, community leaders, youth, artisans, business owners, and government representatives. The study identifies three significant outcomes: (1) the successful integration of batik tulis into the village’s development plan by the local government and Bumdes, (2) the establishment of Woro Srikandi batik tulis as an educational tourism destination, and (3) increased tourism awareness among residents, which has fostered the growth of a creative economy that supports the batik tulis tourism initiative. The findings highlight that development communication serves as a strategic tool for building inclusive discourse, enhancing participation, and cultivating community identity. These insights are crucial for promoting sustainable tourism and the creative economy in rural areas.